Cutaneous Mucormycosis - Karyadi, Erlinda; Agnes, Leoni (PT. Kalbe Farma Tbk., 2022)
Cutaneous mucormycosis is an emerging fungal infection caused by opportunistic fungi from phylum Glomeromycota. This disease is frequently found in poorly controlled diabetic patients and immunosuppressed individuals. It is usually acquired by direct inoculation through trauma.The clinical presentation is nonspecific indurated plaque rapidly evolves to necrosis. Diagnosis should be confirmed by demonstration of the etiological agent and molecular tests. First-line therapy is amphotericin B combined with surgery; second line treatment include posaconazoleand isavuconazole.